Laterally loaded piles with wings : in situ testing with cyclic loading from varying directions - Rudolph, Christina; Grabe, Jürgen (Volume 6: Polar and Arctic Sciences and Technology; Offshore Geotechnics; Petroleum Technology Symposium, 2013)
The application of piles as foundations for offshore wind turbines yields new requirements for the design. Wind and waves induce a cyclic lateral loading on the pile which changes direction corresponding to the meteorological conditions. Cyclic lateral loading on piles results in accumulated displacements, depending on the cyclic load level and load characteristics. The deformation can increase significantly due to a varying loading direction. Under such loading conditions the pile can drift sideways even if the loading is symmetric. Wings attached to the pile shortly below the seabed have been known to reduce deformations on laterally loaded piles as they locally enlarge the diameter on which the soil resistance is activated. They also change the cross-section of the pile from a circular shape to a star-shape. This might reduce the drifting of the pile. A series of large-scale in-situ tests has been carried out in order to identify the effects of changing loading direction as well as the applicability of winged piles to reduce deformations. Two tubular steel piles (one of them equipped with wings) have been installed and subjected to highcyclic lateral loading from varying directions. In this paper the in-situ tests and their results are presented. Copyright